2012
DOI: 10.1371/journal.pone.0037229
|View full text |Cite
|
Sign up to set email alerts
|

Pemetrexed plus Platinum as the First-Line Treatment Option for Advanced Non-Small Cell Lung Cancer: A Meta-Analysis of Randomized Controlled Trials

Abstract: To compare the efficacy and toxicities of pemetrexed plus platinum with other platinum regimens in patients with previously untreated advanced non-small cell lung cancer (NSCLC). Methods: A meta-analysis was performed using trials identified through PubMed, EMBASE, and Cochrane databases. Two investigators independently assessed the quality of the trials and extracted data. The outcomes included overall survival (OS), progression-free survival (PFS), response rate (RR), and different types of toxicity. Hazard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 24 publications
1
31
0
3
Order By: Relevance
“…Non-small cell lung cancer (NSCLC) represents 85% of all lung cancer cases, and most NSCLC patients present with advanced disease with a very poor rate of cure (2,3). Since the 5-year survival of patients with metastatic NSCLC is <15%, prognostic assessment of the patient is essential for the choice of better therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) represents 85% of all lung cancer cases, and most NSCLC patients present with advanced disease with a very poor rate of cure (2,3). Since the 5-year survival of patients with metastatic NSCLC is <15%, prognostic assessment of the patient is essential for the choice of better therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently gemcitabine, with platinum chemotherapy [5]. Even though globally they concluded that the combination of pemetrexed and platinum derivatives was associated to longer OS (HR = 0.91 95% CI: 0.83-1.00), this study should be taken cautiously.…”
mentioning
confidence: 77%
“…These findings raise the possibility that two drugs can and should be used in some groups of older cancer patients in the hope of garnering a survival advantage for them. In nonsquamous cancer patients the combination of pemetrexed and carboplatinum appears to be well tolerated and effective [26]. A subset analysis of a clinical trial comparing carboplatin/pemetrexed to carboplatin/docetaxel showed a favorable toxicity profile for the carboplatin/pemetrexed combination in the elderly subset [27].…”
Section: For Reprint Orders Please Contact: Reprints@futuremedicinecommentioning
confidence: 99%